Fatigue in Multiple Sclerosis: Misconceptions and Future Research Directions - Rudroff, Thorsten; Kindred, John H.; Ketelhut, Nathaniel B. (Frontiers in Neurology, 2016)
Fatigue is one of the most disabling side effects in people with multiple sclerosis (PwMS). While this fact is well known, there has been a remarkable lack of progress in determining the pathophysiological mechanisms behind fatigue and the establishment of effective treatments. The main barrier has been the lack of a unified definition of fatigue that can be objectively tested with validated experimental models. In this ‘perspective article’ we propose the use of the following model and definition of fatigue: the decrease in physical and/or mental performance that results from changes in central, psychological, and/or peripheral factors. These changes depend on the task being performed, the environmental conditions it is performed in, and the physical and mental capacity of the individual. Our definition and model of fatigue outlines specific causes of fatigue and how it affects task performance. We also outline the strengths and weaknesses of commonly used measures of fatigue and suggest, based on our model and definition, new research strategies which should include multiple measures. These studies should be mechanistic with validated experimental models to determine changes in central, psychological, and/or peripheral factors that explain fatigue. The proposed new research strategies may lead to the identification of the origins of MS related fatigue and the development of new, more effective treatments.